COULD IT HAPPEN? Global Warming, Political Coordination Failure and the Extinction of Mankind? - Lane, Jan-Erik (Advances in Social Sciences Research Journal, 2017)
The governments of the countries in the world struggle with climate change and its threatening consequences for mankind chiefly by means of the UN mechanism UNFCCC. The upcoming COP23 global meeting, hosted by Fiji must outline how its three 2015 Paris COP21 objectives are to be promoted and implemented by clearly stated means or tools/tasks for international political governance and national political management. It seems now that only a massive replacement of fossil fuels and wood coal by solar and/or wind power can save mankind from the threat of global warming. How will the governments go about this formidable challenge? This paper presents a tentative estimation of what is involved with regard to the fulfilment of the GOAL II in COP21, in order to show the immensity of the political task of protecting humanity against climate change full disaster, focusing on solar power as the model example.